The impact of parental labor shocks on youths decisions - Oliveira, Júlia Queiroz Maranhão de (2024)
This article aims to examine the impacts of parental shocks, both negative and positive, on the labor market participation of children. A parental shock is defined as a sudden and unexpected change in the employment status of one of the parents, encompassing job loss or gain. Such shocks can trigger cascading effects within the family, affecting the youth. This study explores the dynamics between negative parental shocks (job loss or inactivity) and positive shocks (job gain) and their influence on the participation of young individuals in the labor market. The analysis incorporates various variables related to youth in the labor market, including participation rate and formality. Using a differences-indifferences (diff-in-diff) approach, it was observed that negative shocks increase the participation of young individuals in the labor market, reaching a probability of nearly 0.3 in interviews following the shock, both for biparental and single-parent families. Regarding participation in the formal sector, there is also an increase after negative shocks, with probabilities ranging from 0.2 to 0.25 for single-parent families and approximately 0.3 for biparental families. Concerning positive shocks, a reduction in the participation of young individuals was observed in subsequent PNADc interviews, both for biparental and single-parent families. As for participation in the formal sector after positive shocks, the results were inconclusive.